EFEKTIVITAS PEMBELAJARAN MENGGUNAKAN MEDIA PEMBELAJARAN MACROMEDIA FLASH DALAM MENINGKATKAN PEMAHAMAN KONSEP FISIKA MATERI HUKUM NEWTON - Santih Anggereni; Khairurradzikin Khairurradzikin (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
This research aims to find out general view of conceptual understanding of physics of students X MAS Ashalihin in Gowa regency before and after using Macromedia Flash in learning process. The samples were selected through purposive sampling, instrument used in the form of understanding concept test, observation, and students’ questionnaire responses.The result of the research shows there are differences in students' understanding of physics concepts before the application of macromedia flash with mean score 26.74 and after the application of macromedia flash with mean score 62.38. The result of inferential data analysis reveals tvalue>ttable with tvalue = 3.87 and ttable = 2.04 in significance standard α = 0.05, therefore it can be concluded that the hypothesis is accepted in achieving the increase of conceptual understanding of physic to the students of X MAS class of Ashalihin Gowa regency.